Three new species of trichogrammatidae parasitoids of lepidoptera maniot and eucalyptus defoliators - Brun, Philippe Gabriel; Moraes, George Washington Gomez de; Soares, Lourdes Aragão (Pesquisa Agropecuaria Brasileira, 2014)
Three new species of Trichogramma Westwood from Brazil are described: T. maniçobai, T. caiaposi and T. acacioi. The former two parasita Erinnyis ello eggs (cassava pest) and latter parasitas Psorocampa denticulata eggs (eucaliptus pest). The formation of a new group of Trichogramma for T. caiaposi and T. acacioi is proposed.
Keywords: Trichogramma maniçobai; T. caiaposi; T. acacioi; eggs; parasites; new group for Trichogramma